1930
DOI: 10.1111/j.1469-185x.1930.tb00900.x
|View full text |Cite
|
Sign up to set email alerts
|

The Rgle of Cellulose in Nutrition

Abstract: Summary. The question of the rôle which cellulose plays in nutrition is of particular importance to the agriculturist, since fibre constitutes a very significant part of the normal rations of farm animals. The fibre in plants and feeding stuffs consists of cellulose, admixed with varying amounts of lignocellulose. In the young plant, the cell walls are composed almost wholly of cellulose. The latter is digested in the ruminant tract almost to the same extent as is the carbohydrate component. As the plant matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1953
1953
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…These VFA were generally assumed to be waste products and Woodman (1930) suggested that cellulose gave rise primarily to glucose which was then used as the energy source.…”
Section: Structure Of the Rumenmentioning
confidence: 99%
“…These VFA were generally assumed to be waste products and Woodman (1930) suggested that cellulose gave rise primarily to glucose which was then used as the energy source.…”
Section: Structure Of the Rumenmentioning
confidence: 99%
“…It had long been known that cellulose was fermented in the rumen and that among the end-products were VFA. These VFA were generally assumed to be waste products and Woodman (1930) suggested that cellulose gave rise primarily to glucose which was then used as the energy source.…”
Section: Structure Of the Rumenmentioning
confidence: 99%